Intranasal Midazolam versus Rectal Diazepam for the Management of Canine Status Epilepticus: A Multicenter Randomized Parallel‐Group Clinical Trial. (24th May 2017) - Charalambous, M.; Bhatti, S.F.M.; Van Ham, L.; Platt, S.; Jeffery, N.D.; Tipold, A.; Siedenburg, J.; Volk, H.A.; Hasegawa, D.; Gallucci, A.; Gandini, G.; Musteata, M.; et al.
Abstract : Background: Intranasal administration of benzodiazepines has shown superiority over rectal administration for terminating emergency epileptic seizures in human trials. No such clinical trials have been performed in dogs. Objective: To evaluate the clinical efficacy of intranasal midazolam (IN‐MDZ), via a mucosal atomization device, as a first‐line management option for canine status epilepticus and compare it to rectal administration of diazepam (R‐DZP) for controlling status epilepticus before intravenous access is available. Animals: Client‐owned dogs with idiopathic or structural epilepsy manifesting status epilepticus within a hospital environment were used. Dogs were randomly allocated to treatment with IN‐MDZ (n = 20) or R‐DZP (n = 15). Methods: Randomized parallel‐group clinical trial. Seizure cessation time and adverse effects were recorded. For each dog, treatment was considered successful if the seizure ceased within 5 minutes and did not recur within 10 minutes after administration. The 95% confidence interval was used to detect the true population of dogs that were successfully treated. The Fisher's 2‐tailed exact test was used to compare the 2 groups, and the results were considered statistically significant if P < .05. Results: IN‐MDZ and R‐DZP terminated status epilepticus in 70% (14/20) and 20% (3/15) of cases, respectively ( P = .0059). All dogs showed sedation and ataxia. Conclusions and Clinical Importance: IN‐MDZ is a quick, safe and effective first‐line medication for controlling status epilepticus in dogs and appears superior to R‐DZP. IN‐MDZ might be a valuable treatment option when intravenous access is not available and for treatment of status epilepticus in dogs at home.